Using error bounds to compare aggregated generalized transportation models - Litvinchev, Igor S.; Rangel, Socorro (Springer, 2006)
A comparative study of aggregation error bounds for the generalized transportation problem is presented. A priori and a posteriori error bounds were derived and a computational study was performed to (a) test the correlation between the a priori, the a posteriori, and the actual error and (b) quantify the difference of the error bounds from the actual error. Based on the results we conclude that calculating the a priori error bound can be considered as a useful strategy to select the appropriate aggregation level. The a posteriori error bound provides a good quantitative measure of the actual error.
Keywords: clustering; network models; approximation algorithms